The Role of Sustainable Packaging in Saudi Arabian Supply Chains FMCG: Analyzing Consumer Acceptance and Marketing Strategies for Enhancing Environmental Impact - Bahareth, Aseel; Soliman, Karim (Journal of Ecohumanism, 2025)
Sustainable packaging trends have, therefore, shaped consumers' behavior in the fast-moving consumer goods (FMCG) sector in Saudi Arabia. A quantitative approach has been taken in this present study to test the hypothesis that environmental concern, cost consciousness, and cultural values, along with positive portrayals of sustainable packaging, would influence consumer acceptance and satisfaction and marketing strategies toward the product. By applying partial least squares structural equation modelling (PLS-SEM) to survey data from Saudi consumers, research has demonstrated that environmental concerns drive satisfaction and demand, whereas positive portrayals drive advocacy and consumer perceptions. Other findings point to nuances in the role of cost awareness and cultural values in marketing strategy and brand loyalty. This research provides useful insights to businesses and policymakers on how to combine sustainable practices for environmental impact and consumer engagement in Saudi Arabia.